An analysis of symbols in spanish civil war as seen in For whom the bell tolls by ernest hemingway - Faehusi Telaumbanua; Feby Meuthia Yusuf (Jurnal Ilmiah Langue and Parole, 2017)
The problem in this thesis is the symbols contained in the civil war in Spain. This fight has taken many casualties, death is common, but the soldiers continue to struggle and sacrifice for the hope of victory. The three themes of the struggle about death, sacrifice, and hope are reflected in the symbols of the war. In this writing, literature research is taken as a method of data collection. As for data analysis methods, the authors perform systematic procedures with the understanding of novels, symbols and symbol analysis, as well as semiotic theory. Data collection techniques use documentation techniques in finding data relevant to the subject. In data analysis techniques, the authors use structural techniques by analyzing novels based on the elements that shape them. The results of the research in this thesis are: 1) dynamite is a symbol of death, it can be connected with dynamite properties that can destroy anything around him, here are three Robert who aims to destroy the enemy by installing dynamite, 2) dynamite trigger is a symbol of sacrifice from the The main character, without any trigger, dynamite will not be explosive, Robert in this novel self-criticism to prevent enemies from being able to chase his fleeing friends, 3) the bridge as a symbol of hope, this is connected with the nature of the bridge connecting the two Side, Robert at the end of the story gives hope to his friends to stay safe from the battlefield.